Real-Time In Vivo Detection and Monitoring of Bacterial Infection Based on NIR-II Imaging - Feng, Sijia; Li, Huizhu; Liu, Chang; Chen, Mo; Sheng, Huaixuan; Huang, Mingru; Li, Yunxia; Chen, Jun; Zhang, Jian; Hao, Yuefeng; Chen, Shiyi (Frontiers in Chemistry, 2021)
Treatment according to the dynamic changes of bacterial load in vivo is critical for preventing progression of bacterial infections. Here, we present a lead sulfide quantum dots (PbS QDs) based second near-infrared (NIR-II) fluorescence imaging strategy for bacteria detection and real-time in vivo monitoring. Four strains of bacteria were labeled with synthesized PbS QDs which showed high bacteria labeling efficiency in vitro. Then bacteria at different concentrations were injected subcutaneously on the back of male nude mice for in vivo imaging. A series of NIR-II images taken at a predetermined time manner demonstrated changing patterns of photoluminescence (PL) intensity of infected sites, dynamically imaging a changing bacterial load in real-time. A detection limit around 102 to 104 CFU/ml was also achieved in vivo. Furthermore, analysis of pathology of infected sites were performed, which showed high biocompatibility of PbS QDs. Therefore, under the guidance of our developed NIR-II imaging system, real-time detection and spatiotemporal monitoring of bacterial infection in vivo can be achieved, thus facilitating anti-infection treatment under the guidance of the dynamic imaging of bacterial load in future.